IDENTIFIKASI SENYAWA FLAVONOID EKSTRAK ETANOL AKAR BAJAKAH (Spatholobus littoralisHassk.) - Ade Ferdinan; Elinur Natasa (Jurnal Farmasi IKIFA, 2024)
This study aims to identify flavonoid compounds from ethanol extract of bajakah root using thin layer chromatography (TLC) with mobile phase variations. The results of the phytochemical examination carried out by the shinoda test gave a red color and the H2SO4 test gave an orange-red color, indicating that there were flavonoid compounds.The results of thin layer chromatography using ethyl acetate: methanol (3:2) mobile phase has an Rf value of 0.80, in the mobile phase n-butanol: acetic acid: water (4:1:5) an Rf value of 0.75 indicates the presence of flavonoid compounds. Keywords: Roots of bajakah, Identification, Thin layer chromatography